Insights into the structure and ionic transport in ‘water-in-bisalt’ electrolytes for lithium-ion batteries - Kartha, Thejus R. (Royal Society of Chemistry, 2021)
We investigated the dynamics and transport of lithium-ion water-in-bisalt (WiBS) electrolytes that contain lithium bis(trifluorosulfonimide) (LiTFSI) and lithium triflate (LiOTf) at different concentrations and temperatures using classical molecular dynamics simulations. The presented results are helpful to access the advantages of their use as electrolytes in Li-ion batteries. The structural analysis shows that the Li-ions have analogous interactions with the oxygen atoms of TFSI, OTf- and water. The calculated ionic conductivities from the current autocorrelation function are close to the experimental data for all the concentrations except the lowest one, in which case, the correlated conductivity is close to the experiment. However, the Nernst–Einstein route for calculating ionic conductivity overestimates the values by a reasonably high margin. Ion-cage correlation dynamics show increasing ion-cage lifetimes with increasing concentration, which indicates that the Li-ions remain within the anionic cages for a longer time at higher concentrations. At higher temperatures, this lifetime is seen to decrease. The statistics of non-coordinated Li-ions that are free from TFSI- and OTf- support the ion-cage dynamics.
uGDX
Keywords: lithium-ion; water-in-bisalt; ionic conductivity; Li-ions